The loudest scream - Stine, R. L. (Pocket Books New York, 1996)
In the wake of several terrible accidents at Fear Park, Diedre Bradley pursues a relationship with the intense and mysterious Robin Fear and learns of his plans to destroy the park, even at the cost of Diedre's life